BADAN USAHA MILIK DAERAH SEBAGAI SARANA MEWUJUDKAN OTONOMI DAERAH - Surahman Surahman; Asri Lasatu; Asriyani Asriyani (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2020)
Establishment of Regional Owned Enterprises (BUMD) An effort to reduce the dependence of local governments on balancing funds from the central government. This Regionally Owned Enterprise is mostly or wholly owned by regions of wealthy regions. This BUMD is a government instrument that has a role to develop the regional and even national economy. The existence of BUMD in successful regional economic activities is a new thing, but has been going on for a long time. The obligation to establish BUMD is to carry out regional development through services to the community, implementing public benefits and increasing the level of local government. The purpose of this study is to determine the legal description of BUMD in taking legal actions and what factors are obstacles for BUMD to achieve their orders. The research method used is normative juridical research method.